Svetna in sveta zgodovina v razmišljanjih visokosrednjeveških teologov - Ambrožič, Matjaž (Bogoslovni vestnik, 2024)
The relationship between ‘sacred’ and ‘profane’ history is complex. It is basically an attempt to answer the question concerning the relationship between human history and the history of salvation. Otto of Freising defended the idea of the transmission of the Roman Empire through the Byzantines to the Franks and through them to the German emperors. Rupert of Deutz divided the action of the Most Holy Trinity into three ages: from the creation of light to the fall of the first man; to the passion of Jesus Christ; from the resurrection of Christ to the end of time. Anselm of Havelberg held that history from the first Adam to the last Adam ‘progressed’ according to the sequence of the different ages. Hugo of St. Victor divided universal history into three kingdoms: the kingdom of natural law (from creation); the kingdom of the Hebrew law (from Abraham); the kingdom of grace (from Christ). Joachim da Fiore represented the idea of an unfolding history that runs from God’s creation of the world through Jesus Christ and the Church Age to the ‘third age’ of the Holy Spirit. The three ages (states) of the world correspond to the persons of the Most Holy Trinity.
Keywords: Anselm of Havelberg; Anzelm Havelberški; Hugo od sv. Viktorja; Hugo of St. Victor; Joachim da Fiore; Joahim iz Fiore; Oto iz Freisinga; Otto of Freising; Rupert iz Deutza; Rupert of Deutz; sacred and profane history; sveta in svetna zgodovina